2022
DOI: 10.3389/fmars.2022.870792
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Stages of North Atlantic Laminaria digitata (Phaeophyceae) Exhibit Trait-Dependent Thermal Adaptation Along Latitudes

Abstract: Kelp forests in the North Atlantic are at risk of decline at their warm temperature distribution margins due to anthropogenic temperature rise and more frequent marine heat waves. To investigate the thermal adaptation of the cold-temperate kelp Laminaria digitata, we sampled six populations, from the Arctic to Brittany (Spitsbergen, Tromsø, Bodø [all Norway], Helgoland [Germany], Roscoff and Quiberon [both France]), across the species’ entire distribution range, spanning 31.5° latitude and 12-13°C difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 86 publications
2
4
0
Order By: Relevance
“…In addition, some of these candidate loci have important metabolic and cellular functions that could be involved in adaptive responses. While our findings support the hypothesis that SST is driving the adaptive response of L. digitata, consistent with previous heat stress experiments performed on the same populations (Liesner et al, 2020;Schimpf et al, 2022) and genome scans of other kelp species (Guzinski et al, 2020;Mao et al, 2020;Vranken et al, 2021), it is important to note that confounding factors may also be at play. This is particularly relevant in the present study because of the phylogeographical history of the species along the North Eastern coast of the Atlantic which indicated that L. digitata is composed of two different clusters (Neiva et al 2020).…”
Section: Signals Of Adaptive Response At the Southern Marginsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, some of these candidate loci have important metabolic and cellular functions that could be involved in adaptive responses. While our findings support the hypothesis that SST is driving the adaptive response of L. digitata, consistent with previous heat stress experiments performed on the same populations (Liesner et al, 2020;Schimpf et al, 2022) and genome scans of other kelp species (Guzinski et al, 2020;Mao et al, 2020;Vranken et al, 2021), it is important to note that confounding factors may also be at play. This is particularly relevant in the present study because of the phylogeographical history of the species along the North Eastern coast of the Atlantic which indicated that L. digitata is composed of two different clusters (Neiva et al 2020).…”
Section: Signals Of Adaptive Response At the Southern Marginsupporting
confidence: 91%
“…Together, these findings support that genetic drift relative to selection is an important component of the contemporary evolution of this population. This is in line with earlier reports, indicating low levels of genetic diversity at microsatellites in Helgoland (Liesner et al, 2020;Fouqueau, 2021) and signals of local adaptation to temperature that became less clear when comparisons have been made with gametophytes from Helgoland rather than Quiberon (Schimpf et al, 2022). Several factors linked to the geographical isolation of the population and frequent high summer temperatures that both reduced or even inhibited the reproduction of individuals and cause severe bottlenecks (Bartsch et al, 2013) are likely to be involved in its genetic impoverishment.…”
Section: When Genetic Drift Overwhelms Local Selectionsupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, both thermal history and genetic differentiation can cause population‐specific responses to ocean warming (Liesner et al, 2020; Sánchez de Pedro et al, 2022). Kelp responses to warming can depend on previous thermal exposure (Gauci et al, 2022), which tends to differ across populations, leading to intraspecific differences in thermal tolerance (Becheler et al, 2022; Martins et al, 2020; Schimpf et al, 2022; Strasser et al, 2022). The Salish Sea is a large and complex estuarine system, with sea surface temperatures that can span >8°C across sites that are <100 km apart, depending on the tides, currents, river inputs, and distance from the Pacific Ocean (MacCready et al, 2021).…”
Section: Introductionmentioning
confidence: 99%